COMMUNITY COLLABORATION IN UMKM SOCIALISATION: A SERVICE STRATEGY FOR VILLAGE INDEPENDENCE - Sidderatul Akbar; Wilda Rizkiyahnur Nasution; Nashran Azizan; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2024)
Community participation in the development of Micro, Small and Medium Enterprises (MSMEs) is essential to support the sustainability of the village. There are situations, where local government, civil society, academia and businesses interact systematically so that effective support is available for the purpose of MSMEs. They include training, consulting, technology, and market access. All these are targeted at increasing the ability of the MSMEs to expand and develop sustainably. Through this, interlinking horizontal structures amongst the MSMEs can be established creating positive impact on the economy of the village. There is always efficiency that exists when working in partnership within the MSMEs and they improve competitiveness. In addition, this partnership also creates chances for the MSMEs to enhance the local market with more qualified products which can become local landmarks and also attract shoppers within the region and beyond. The collaboration promotes a spirit of business cooperation among businesspersons and helps son comprehensiveness in business practice. They allow MSMEs to assist each other and pool resources, which is crucial for weathering economic storms. As observed in the intervention through the community collaboration in this service strategy, there are great positive long term benefits particularly in instilling mental independence and sustainability of the villages. Such participation also enhances or fosters a sense of belonging to and the drive to develop the village among its inhabitants and builds a coherent social structure. All necessary economic, social and cultural resources are available to a village, enabling it not only to subsist but also to prosper and adjust to global changes and this making the essence of community participation an important strategy for development.